2009
DOI: 10.1007/bf03160978
|View full text |Cite
|
Sign up to set email alerts
|

Neuroleptic malignant syndrome developing after acute overdose with olanzapine and chlorpromazine

Abstract: Neuroleptic malignant syndrome (NMS) is a relatively uncommon side effect that may develop after a recent increase in the therapeutic dose of an antipsychotic medication or the addition of a new agent in therapeutic doses.Case Report: We report a case of NMS developing in a 36-year-old female patient 2 days following deliberate self-poisoning with 30 ϫ10-mg olanzapine tablets, 7 ϫ100-mg chlorpromazine tablets and an unknown amount of escitalopram. These were the patient's own medications. She had not been taki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…However, recent studies found no significant difference between typical and atypical APDs in the emergence of TD (Miller et al 2008;Correll and Schenk 2008). Similarly, there is increasing evidence that treatment with atypical APDs may also result in NMS (El-Gaaly et al 2009;Morris et al 2009;Trollor et al 2009). …”
Section: Toxicity Studiesmentioning
confidence: 94%
“…However, recent studies found no significant difference between typical and atypical APDs in the emergence of TD (Miller et al 2008;Correll and Schenk 2008). Similarly, there is increasing evidence that treatment with atypical APDs may also result in NMS (El-Gaaly et al 2009;Morris et al 2009;Trollor et al 2009). …”
Section: Toxicity Studiesmentioning
confidence: 94%
“…In NMS (and parkinsonism‐hyperpyrexia syndrome), a majority of cases do not ever develop the degree of hyperthermia usually associated with morbidity (i.e., 39.5°C or greater), even with only conservative treatment. Also, deterioration of clinical status and morbidity and mortality occur in the absence of a degree of hyperthermia that is injurious: deterioration of renal, mental, neurological, and respiratory function, despite a maximum temperature of less than 39°C, is documented in many reports 5, 83, 102, 121. To regard NMS as a primarily hyperthermic syndrome is an inadequate explanatory model and may lead to underestimation of clinical severity or exclusion of NMS because the patient is not hyperthermic.…”
Section: Discussionmentioning
confidence: 99%
“…Since activation of 5‐HT2A receptors worsens, and antagonism reduces, the consequences of most forms of hyperthermia,78–80 5‐HT2A agonism is a undesirable property. There is disagreement concerning bromocriptine's efficacy, and some evidence supports the notion that it could worsen NMS 81–83. Apomorphine is the only clinically available DA agonist that is also a 5‐HT2A antagonist and, therefore, may be preferable to bromocriptine 84, 85.…”
Section: Measurement and Definition Of Hyperthermiamentioning
confidence: 99%
“…The syndrome is initiated by the addition of a new drug to pre-existing treatment or by increasing the dosage of the used drug. Clinical findings include fever, tachycardia, muscular rigidity (leadpipe type) and increased muscle tone, altered mental status, leucocytosis and increased serum creatinine phosphokinase (CPK) levels (1). NMS should be suspected in case there is autonomic instability, neuromuscular or central nervous system dysfunction in patients.…”
Section: Introductionmentioning
confidence: 99%